Efektivitas Bobath Exercises dan Massage pada Pasien Cerebral Palsy - Suharto, Suharto; Arpandjam'an, Arpandjam'an; Suriani, Suriani (FORUM ILMIAH KESEHATAN, 2022)
The main problems of the subjects of this study were spasticity and the ability to sit, due to non-progressive brain disorders. This disorder is accompanied by an inability to control posture and balance. This study aims to determine the effectiveness of Bobath exercise and massage to reduce spasticity and improve the sitting ability of cerebral palsy patients. This type of research is an experimental one group pretest-posttest design. The research subjects were 17 cerebral palsy patients who met the research criteria. Spasticity and sitting ability were measured by observation and examination, then analyzed by the Wilcoxon test. The p-value for the difference between before and after the intervention was 0.001, which means there was a significant difference. Furthermore, it was concluded that Bobath exercise and massage were effective in reducing spasticity and increasing the sitting ability of cerebral palsy patients.Keywords: cerebral palsy; Bobath exercises; massages; spasticity; sitting abilityABSTRAK Problem utama subjek penelitian ini adalah spastisitas dan kemampuan duduk, karena gangguan otak yang non progresif. Gangguan ini disertai ketidakmampuan mengontrol postur dan keseimbangan. Penelitian ini bertujuan untuk mengetahui efektifitas Bobath exercsise dan massage untuk menurunkan spastisitas dan meningkatkan kemampuan duduk pasien cerebral palsy. Jenis penelitian ini adalah eksperimen dengan desain one group pretest-posttest. Subyek penelitian adalah 17 pasien cerebral palsy yang memenuhi kriteria penelitian. Spastisitas dan kemampuan duduk diukur dengan observasi dan pemeriksaan, lalu dianalisis dengan uji Wilcoxon. Nilai p untuk perbedaan antara sebelum dan sesudah intervensi adalah 0,001, yang berarti ada perbedaan secara signifikan. Selanjutnya disimpulkan bahwa Bobath exercise dan massage fektif untuk menurunkan spastisitas dan meningkatkan kemampuan duduk pasien cerebral palsy.Kata kunci: cerebral palsy; Bobath exercise; massage; spastisitas; kemampuan duduk